Performance analysis of male handball goalkeepers at the World Handball championship 2015 - Hansen, Clint; Sanz-Lopez, Fernando; Whiteley, Rodney; Popovic, Nebojsa; Ahmed, Hosny Abdelrahman; Cardinale, Marco (Biology of Sport, 2017)
Goalkeepers have a very important role in handball. In coaching communities it is well recognized that goalkeepers’ performances can predict team ranking in major tournaments. Despite this, few studies have been conducted on elite goalkeepers participating in World Championships. Therefore, the purpose of this study was to analyse goalkeepers’ save performance during the 88 matches of the 2015 men’s World Championships tournament. Goalkeepers from 24 national teams were analysed using a tracking camera system and bespoke software (Prozone Handball V.1.2, Prozone, Leeds, UK). The purpose of this study was to examine time-motion performance parameters and to evaluate the save rates for each goalkeeper. The mean total distance covered in a game by the goalkeepers was 1634±999 m. Goalkeepers spent most of the time walking or standing. The total amount of shots to the goal was 6893, with a mean save percentage of 30% (2088 saves). A significant relationship was identified between the goalkeepers’ save statistics and the final team rankings. The save rate is important for teams to achieve a higher ranking, and therefore the selection and training of goalkeepers requires more than just assessing physical abilities. The throwing distribution and success/save rate during the Qatar 2015 Men Handball World Championships suggest strong and weak parts of the goal area, and coaches can use this information to adjust their training approaches for both goalkeepers and shooters.